O papel da odontologia legal na identificação humana em vítimas de desastres em massa: revisão de literatura. - RAMALHO, Lorena Cedran (2021)
Human identification is one of the main activities developed by Forensic Dentistry. Mass disasters are catastrophic accidents, natural or generated through the action or influence of human beings, which constantly result in a high number of fatalities. Dental methods are widely used in this case, mainly through the dental elements, as the teeth have high resistance to destruction, to high temperatures and pressure variations, which enable the identification in bodies that are in bad condition of putrefaction, carbonized, fragmented and in an advanced stage of destruction. This article aims to analyze and debate the importance and role of Forensic Dentistry through a literature review, between the link of the OdontoLegal identification method and cases of mass disasters. The dental method of identification showed success in several cases, where other techniques such as fingerprinting was not possible, as the integrity of the bodies was compromised. Thus, the identification process through Legal Dentistry is precise, fast, practical, reliable, simple, low-cost and resolvable, especially in cases of mass disasters.